Pseudocapacitive brookite phase vanadium dioxide assembled on carbon fiber felts for flexible supercapacitor with outstanding electrochemical performance. (March 2022) - Zhang, W.J.; Sun, M.X.; Yan, X.H.; You, M.Y.; Li, Y.L.; Zhu, Y.H.; Zhang, M.Y.; Zhu, W.; Javed, M.S.; Pan, J.M.; Hussain, S.
Highlights: The mixed acid was firstly employed on CFF to enrich its functional surface. VO2 (B) nanoribbons were assembled on CFF via a novel chemical bath deposition. CFFVO-60 exhibits good electrochemical performance in three/two-electrode system. The FASC maintains excellent stability while it was bent and tailored. Two FASCs in series lights a LED bulb of 1.8 v for 2 min. Abstract: As a supercapacitor electrode, brookite phase VO2 (B) possesses characteristics, such as facile preparation, safety and high pseudo-capacitance, but reveals its inherent drawback of high resistivity. Designing reasonable nanostructure using carbon fiber paves the way for improving its electrochemical performance and broadening its application in supercapacitors. In this work, one-dimensional VO2 (B) nanoribbons are successfully synthesized by introducing carbon fiber felt (CFF) with three-dimensional structure via a chemical bath deposition. The indispensable growth substrate (CFF) is useful for optimizing the morphology of VO2 (B) nanoribbon, effectively demonstrating its nano-effects, shortening the ion/electron diffusion paths, reducing the resistivity, increasing the specific surface area and improving its structural stability. The results show that the specific capacitance of optimal CFFVO-60 (CFF@VO2 composite with 60 min deposition time) can reach 1248 mF/cm 2 at the current density of 1 mA/cm 2, which is much higher than 451 mF/cm 2 of VO2 (B) membrane. Furthermore, the prepared CFFVO-60 exhibits outstanding Faraday pseudocapacitive behavior in positive potential. The flexible all-solid-state asymmetric supercapacitor (FASC) is assembled using ultra-thin carbon nanosheets (CNS) as the negative electrode and the CFFVO-60 as the positive electrode, exhibiting excellent electrochemical performance. Compared to previous literatures, the energy density of our work is enhanced by 15–20%. Finally, the successful lighting LED indicates good practicality of the device. Graphical abstract: Image, graphical abstract